2022
DOI: 10.1021/acs.jproteome.2c00020
|View full text |Cite
|
Sign up to set email alerts
|

PPI-Affinity: A Web Tool for the Prediction and Optimization of Protein–Peptide and Protein–Protein Binding Affinity

Abstract: Virtual screening of protein–protein and protein–peptide interactions is a challenging task that directly impacts the processes of hit identification and hit-to-lead optimization in drug design projects involving peptide-based pharmaceuticals. Although several screening tools designed to predict the binding affinity of protein–protein complexes have been proposed, methods specifically developed to predict protein–peptide binding affinity are comparatively scarce. Frequently, predictors trained to score the aff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
34
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(54 citation statements)
references
References 75 publications
1
34
0
Order By: Relevance
“…The scoring functions can be roughly divided into four categories: force-field-based, empirical, knowledge-based, and machine-learning-based [38]. HDOCK, HawkDock, and PPI-Affinity use knowledge, force field, and machine learning-based scoring functions, respectively [24][25][26]. Thus, in addition to HDOCK, HawkDock and PPI-Affinity were used to determine the optimal docking model.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The scoring functions can be roughly divided into four categories: force-field-based, empirical, knowledge-based, and machine-learning-based [38]. HDOCK, HawkDock, and PPI-Affinity use knowledge, force field, and machine learning-based scoring functions, respectively [24][25][26]. Thus, in addition to HDOCK, HawkDock and PPI-Affinity were used to determine the optimal docking model.…”
Section: Discussionmentioning
confidence: 99%
“…For the prefusion protein, the top 20 docking models were determined from the generated models at each antigenic site based on the docking score of HDOCK, and a total of 120 docking models were created. In addition to HDOCK, two independent scoring functions, HawkDock (http://cadd.zju.edu.cn/hawkdock/, accessed on 15 February 2022) and PPI-Affinity (https://protdcal.zmb.uni-due.de/PPIAffinity/BA/12 19/, accessed on 16 September 2022), were used to rescore the docking models generated by HDOCK [25,26]. The optimal models for the prefusion protein were selected based on the HDOCK, HawkDock, and PPI-Affinity ranking.…”
Section: Protein-protein Docking and Optimal Docking Model Selectionmentioning
confidence: 99%
“…Machine learning methods, from simplest linear regression to deep learning (Seal, 1967;Cortes and Vapnik, 1995;Tin Kam Ho, 1995;Breiman, 1996;Friedman, 2002;LeCun et al, 2015;Goodfellow et al, 2016), have been developed for decades and are implemented in science, finance, healthcare, and other fields (Dixon et al, 2020;Guo et al, 2020;Varoquaux and Cheplygina, 2022;Zhang et al, 2022). In structural biology, machine learning methods have been used to predict the structure of proteins based on their amino acid sequences, design new molecules for enzyme inhibition, and predict the protein-protein interactions (Vamathevan et al, 2019;Baek et al, 2021;Jumper et al, 2021;Romero-Molina et al, 2022). In this section, we focus on regression models for protein-protein interaction prediction (Table 2).…”
Section: Machine Learning Methodsmentioning
confidence: 99%
“…The ensemble model achieved an R p of 0.853 on SKEMPI dataset. PPI-Affinity is a web tool that predicts the binding affinity using support vector machine and other classic machine learning models (Romero-Molina et al, 2022). Accepting thousands of features generated by ProtDCal as input (Romero-Molina et al, 2019), the model showed a performance of R p = 0.77 on SKEMPI dataset.…”
Section: Structure-based Methodsmentioning
confidence: 99%
“…Finally, the prediction of structures and binding affinities seem to be on two independent tracks at the moment-some tools are good for sampling bound states and others for rank-ordering them by binding affinity (Cunningham et al, 2020;Chang and Perez, 2022a;Motmaen et al, 2022). While development in affinity prediction has lagged behind the structure prediction problem, there is a recent increase in the number of methods available, some of them now available as webservers with promising accuracy (Romero-Molina et al, 2022). It is feasible to think that as binding affinity databases increase in size and accuracy, these two independent pieces will be trained together.…”
Section: Machine Learningmentioning
confidence: 99%